Irradiation-induced telomerase activity and gastric cancer risk: a case-control analysis in a Chinese Han population - Wang Zizhong; Shen Shuqun; Nan Jing; Ge Naijian; Qiao Qing; He Xianli; Yang Yefa; Bao Guoqiang (BMC Cancer, 2010)
Abstract Background Telomerase expression is one of the characteristics of gastric cancer (GC) cells and telomerase activity is frequently up-regulated by a variety of mechanisms during GC development. Therefore, we hypothesized that elevated levels of activated telomerase might enhance GC risk due to increased propagation of cells with DNA damage, such as induced by γ-radiation. Methods To explore this hypothesis, 246 GC cases and 246 matched controls were recruited in our case-control study. TRAP-ELISA was used to assess the levels of telomerase activity at baseline and after γ-radiation and the γ-radiation-induced telomerase activity (defined as after γ-irradiation/baseline) in cultured peripheral blood lymphocytes (PBLs). Results Our data showed that there was no significant difference for the baseline telomerase activity between GC cases and controls (10.17 ± 7.21 vs. 11.02 ± 8.03, p = 0.168). However, after γ-radiation treatment, γ-radiation-induced telomerase activity was significantly higher in the cases than in the controls (1.51 ± 0.93 vs. 1.22 ± 0.66, p < 0.001). Using the median value of γ-radiation-induced telomerase activity in the controls as a cutoff point, we observed that high γ-radiation-induced telomerase activity was associated with a significantly increased GC risk (adjusted odds ratio, 2.45; 95% confidence interval, 1.83-3.18). Moreover, a dose response association was noted between γ-radiation-induced telomerase activity and GC risk. Age, but not sex, smoking and drinking status seem to have a modulating effect on the γ-radiation-induced telomerase activities in both cases and controls. Conclusion Overall, our findings for the first time suggest that the increased γ-radiation-induced telomerase activity in PBLs might be associated with elevated GC risk. Further confirmation of this association using a prospective study design is warranted.